Congenital liver hemangioendothelioma complicated with mild polyhydramnios during pregnancy: A case report - Marzieh Lotfalizadeh; Habibeh Ahmadi; Mansoureh Mohammadnezhad (Mashhad University of Medical Sciences, 2021)
Introduction: Hepatic Hemangioma in infants is a mass with good prognosis which can be followed by life threatening complications such as heart failure with high output, Kasabach-Merritt Syndrome and hydrops. In other cases with no fetal, maternal and placental causes for poly hydramnios, hepatic Hemangioma should be considered. In this report, a case of large infant's liver hemangioendothelioma complicated with mild polyhydramnios is presented that led to the improvement of infant by intervention and timely treatment.Case presentation: The patient was a 35 years old woman para 2 with one previous cesarean section. She referred with mild Poly hydramnios in 27th week of gestation. A 56×61 mm sized hypo echogenic & hetrogenic hepatic mass contained with  micro calcification particles in the posterior right liver lobe was diagnosed for the fetus. At 36th week of gestation, planned cesarean was done. After urgent ultrasound, the baby was operated and resection of the tumor was performed. Pathological report showed hepatic hemangioendothelioma. The infant undergone ....... treatment due to the residue. During next follow up, baby was completely recovered and had normal growth & development.Conclusion: In the cases of diagnosis of poly hydramnios and echogenic mass probably with hepatic origin, then Hepatic Hemangioendothelioma may be considered for the infant. Clinical evaluation and early intervention if needed should be performed to prevent cardiovascular complication, and pregnancy termination should be performed to prevent infantile sever complication as soon as lung maturation. Urgent surveillance should be performed immediately after delivery. We should have needed preparation because this tumor is treatable in many cases.